PROSES PEMBELAJARAN REMEDIALMATA DIKLAT PERALATAN DAN BAHAN REFRIGERASI:Penelitian Tindakan Kelas Terhadap Peserta Diklat Program Teknik Pendingin danTata Udara Tingkat 1 SMK TI Pembangunan Tahun Ajaran 2006/2007 - Tatang Rochendi, - (2007)
Tatang Rochendi (2007). "Remedial Learning Process on the subject of equipment and material refrigeration (an action research classroom to student of technical refrigeration and air conditioning On 1st grade SMK TI Pembangunan, academic year 2006/2007 )." Script : Mechanical Enginering Education Departement, The Faculty of Technology and Vocational Education, Indonesia of Education University. This research to obtain the empirical information about influence of Remedial Learning on the subject of equipment and material refrigeration (EMR). On this subject of equipment and material refrigeration, about refrigerant and pipe drawing that aim this remedial learning. Respondence of this research are student on 1st grade technical refrigeration A SMK TI Pembangunan Cimahi amount 34 respondents. This research methode that used action classroom research. The technic of collecting data was did by writing test, every finished remedial learning cycle. The research instruments used was drawing example sheet and essay test. On drawing example instrument was judgement or evaluated by leader of majoring technical refrigeration and air conditioning SMKN I Cimahi. The result of instrument test was get validity analysis, 20 item valid and 4 item not valid that number are 13,14,23 and 24. validity was obtained from result tcount > ttabel (ttabel=1,69 (t0,95;33)).The instrument of reliability was obtained result 0,877. On analize different item was obtained 4 item with bad criteria and for analize of difficult item was obtained 1 item difficult. Based on result of research, before remedial learning was found more student had value under mastery standart (=603; 70 (scala of 100)) in refrigerant matery and pipe drawing. On refrigerant matery, values average is 6,3 and pipe drawing matery is 6,4. Test item for refrigerant matery was used to obtain data amounting 20 item, while to obtain data from pipe drawing matery that used drawing example sheet. Average value refrigerant matery after remedial learning is 8,7 (97,06 % passed) and pipe drawing matery is 7,3 (85,29 % passed). The conclussion in this research is remedial learning was did in any cycle on classroom can solve student achievement problem. This have been seen from student achievement improvement that was obtained for participated every cycle on remedial learning.